Spirulline as protein source: biotechnological aspects - Czapiński, Janusz (Committee on Biotechnology PAS, 1989)
Chernical composition (proteins, lipids, carbohydrates, minerals, vitamins etc.) of a multicellular (alga). Spirulline has been reported. Industrial installations for mass cultivation are described and the technology for utilization of dry biomass In food and fodder production is outlined.
Keywords: biotechnology